SOSIALISASI PENGGUNAAN TEMPAT CUCI TANGAN OTOMATIS DI MUSHOLA BAITUR RAHIM - Ahmad Yanie; Junaidi; Fadly Ahmad Kurniawan; Indra Roza; Din Aswan Ritonga; Eddy Koto (HIMPUNAN DOSEN GEMILANG INDONESIA, 2021)
For Muslims, apart from places of worship, mosques or prayer rooms are also a form of unity, brotherhood and become the center of activity for Muslims. Congregational prayers that are carried out in mosques or in prayer rooms are not only intended for worship, but can also foster a sense of brotherhood and solidarity among Muslims. Our community service from several lecturers at Universitas Harapan Medan is by providing an automatic handwashing device. This socialization aims to make it easier for people to wash their hands automatically at the Baitur Rahim prayer room. The result of this community service is a useful tool for the community to use in washing their hands without touching the water faucet.